14.77 MeV neutron-induced nuclear reaction cross sections for zinc, yttrium, and molybdenum targets*S. D. Dhole and V. N. Bhoraskar gratefully acknowledge the financial assistance given by SERB-DST, New Delhi sanction number: EMR/2017/002497 for research in the field of neutron-induced nuclear reactions. (1st March 2023) - Ganesapandy, T.S.; Bholane, G.T.; Patil, S.H.; Dahiwale, S.S.; Bhoraskar, V.N.; Dhole, S.D.
Abstract: The cross sections for neutron-induced nuclear reactions on natural zinc, yttrium, and molybdenum targets were measured at a neutron energy of 14.77 ± 0.17 MeV using the activation technique, offline gamma-ray spectrometry, and a detailed covariance analysis. The uncertainty in the statistical model calculations of cross sections for the ( n, 2 n ), ( n, p ), ( n, α ), and ( n, γ ) reactions with natural zinc, yttrium, and molybdenum at neutron energies from 13 to 17 MeV was calculated using the TALYS-1.96 nuclear code. The measured cross sections of the present study were compared with the experimental cross sections reported in the EXFOR database, the cross sections were calculated with the TALYS-1.96 and EMPIRE-3.2.3 nuclear codes and the evaluated nuclear data from the TENDL-2019, JENDL-5, and ENDF/B-VIII.0 libraries.